„Poznań został poza nami / My w Rawiczu za kratami”. Codzienność w obozach NKWD i Zakładzie Karnym w Rawiczu w świetle poezji więziennej - Bittner, Karolina (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article analyses a collection of poems written by a female prisoner of NKVD camps in Rembertów and Poznań and the Rawicz Prison. It is a moving source and a personal testimony to the Stalinist period and, at the same time, one of few surviving source materials from the NKVD camp in Poznań. While there are many anthologies of poems about the German occupation, and the martyrdom in Nazi camps or prisons, both by famous poets and unknown authors-amateurs, the bibliography of Soviet and NKVD camps and Stalinist prisons is brief. Thus, it is crucial to examine the discussed 24-page notebook, filled with poems and fragments of prison songs from Stalinist Poland.